KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU PAI DI SMP AN NASHR - Siti Muawanatul Hasanah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2024)
The principal's leadership plays a very important role in advancing the institution he leads. The principal is then responsible for directing and supervising the teachers. This increase in teacher professionalism will be more successful if the teacher implements it with his own abilities and efforts. However, teachers often still need the help of others because they do not understand the types of procedures and mechanisms needed to access various resources to improve their abilities. This is where the leadership of the madrasa head is needed to improve the professionalism of PAI teachers at An Nasr Middle School. In this paper, the researcher chooses the type of qualitative research case study, using data collection techniques in the form of observation, interviews, and recordings. Data analysis techniques determine the validity of the data through data presentation, data reduction, data validation, use of credibility, including expansion of participation, persistence of observation. , triangulation, adequacy of references, and peer review through discussion. Based on the results of the study, it was concluded as follows: Teachers at SMP An Nasr have achieved pedagogic, personal, professional and social competencies, although there are still teachers who are not optimal. The type of religious school principal is charismatic and democratic. Efforts made by principals to improve teacher professionalism include: involving teachers in training, disciplining, supervising, providing new insights and setting a good example. Supporting factors include adequate facilities, incentives and disincentives. Disincentives include: Insufficient funds, teachers themselves do not want to fulfill their potential.